Instructional Supervision and the Pedagogical Practices of Secondary School Teachers in Uganda - Malunda, Paul; Onen, David; Musaazi, John C. S.; Oonyu, Joseph (Journal of Education and Practice, 2016)
This paper looks at the effect of instructional supervision by school authorities on the pedagogical practices of teachers in public secondary schools in Uganda. To date, research into this field in the country has focused more on the technicalities of supervision rather than on how the teachers have been responding to it. The study employed a descriptive cross-sectional survey design, in which both quantitative and qualitative methods of data collection and analysis were applied. Study respondents included 934 teachers randomly selected from 95 public secondary schools, 76 head teachers, and two officials from the Directorate of Education Standards of the Ministry of Education and Sports. Ordered logistic regression technique was used to establish the effect of instructional supervision on the pedagogical practices of teachers. Findings of the study revealed that both classroom observation (odd ratio=4.1; p=0.000<0.05) and portfolio supervision (odd ratio=2.3; p=0.000<0.05) have statistically significant effect on the pedagogical practices of teachers in public secondary schools in Uganda. Furthermore, the study established that school authorities were inadequately carrying out instructional supervision, thereby leaving teachers to employ ineffective pedagogical practices. The study concluded that teachers’ pedagogical practices are dependent on the manner in which they are supervised, other factor notwithstanding. Therefore, in order to augment the pedagogical practices of teachers, school inspection by the Directorate of Education Standards should be increased and regular in-service training needs to be provided to head teachers as well as subject heads on how to conduct classroom observations and portfolio supervision in schools.
Keywords: Instructional supervision; Classroom observations; Portfolio supervision; Pedagogical practices